Anti-Corruption Theology: A Kalam and Sufism Approach to Moral and Spiritual Crisis - Amir Gufron; M. Agus Wahyudi; Sidiq Rahmadi; Zaenal Muttaqin (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Corruption is a multidimensional problem rooted not only in weaknesses of legal systems and institutional governance, but also in the moral and spiritual crisis of individuals. Within this context, the Islamic intellectual tradition, particularly kalam and Sufism, offers a normative and ethical framework for strengthening anti-corruption efforts. This study analyzes the construction of anti-corruption theology in the tradition of kalam and examines the internalization of Sufi values as a preventive foundation for personal integrity and public ethics. Using a qualitative library research approach, the study examines classical and contemporary theological sources alongside key Sufi concepts. The findings indicate that kalam establishes an ethical foundation for anti-corruption through the interrelation of qadar divine decree, moral freedom, taklif moral responsibility, and divine justice adl. The doctrine of kasb in Asharite theology and the emphasis on moral rationality in Maturidite thought reject fatalism and affirm human accountability for corrupt acts, which bear moral and eschatological consequences. The concept of hisab further nurtures transcendental accountability beyond formal legal control. Sufism complements this framework through spiritual purification tazkiyat al nafs and inner awareness, fostering internal moral restraint. The integration of kalam and Sufism thus provides a comprehensive ethical and spiritual foundation for sustainable anti-corruption efforts.